THE TEACHERS' CLINIC. - Carson, A. B.; Griffin, Charles H.; Campfield, William L.; van Voorhis, Robert H. (The Accounting Review, 1958)
Abstract The size, diversity, and complexity of financial activities of present day Federal Government and the need for efficient management and reporting of these activities is of vital concern for every citizen. A purposeful, productive campaign has been underway for some ten years to modernize the entire concept of management in government. This movement has been spearheaded by officials within government and has received impetus and support from citizens' groups, notable among which are the various Hoover Commission Task Forces. Each individual, each institution, and each collective group of individuals has a responsibility to contribute to the effort of achieving effective management of taxpayers' money. Colleges and universities can be particularly helpful and can contribute substantially to this effort by expanding their curricula to include more comprehensive instruction with respect to the application of modern management principles and practices, especially as these relate to activities of the Federal Government. The writer has presented in this paper the framework of a suggested graduate course which would emphasize the management controls necessary to carry out effectively objectives of the legislative and executive branches of the Federal Government. The suggested course might well supplement or complement other Business Administration, Political Science, or Public Administration offerings customarily given by colleges and universities.